Differences in the Origin of Philosophy between Chinese Medicine and Western Medicine： Exploration of the Holistic Advantages of Chinese Medicine - 孙大志 李绍旦 刘毅 张印 梅荣 杨明会 (Chinese journal of integrative medicine, 2013)
To explore advantages of Chinese medicine （CM） by analyzing differences in the origin of philosophy for human health between CM and Westem medicine （WM）. Methodologically, a distinctive feature of CM is its systems theory, which is also the difference between CM and WM. Since the birth of CM, it has taken the human body as a whole from the key concepts of ＂qi, blood, yin-yang, viscera （Zang-Fu）, and meridian and channel＂, rather than a single cell or a particular organ. WM evolves from the Westem philosophic way of thinking and merely uses natural sciences as the foundation. The development of WM is based on human structures, or anatomy, and therefore, research of WM is also based on the way of thinking of decomposing the whole human body into several independent parts, which is the impetus of promoting the development of WM. The core of CM includes the holistic view and the dialectical view. Chinese herbal medicines contain various components and treat a disease from multiple targets and links. Therefore, Chinese herbal medicines treat a diseased state by regulating and mobilizing the whole body rather than just regulating a single factor, since the diseased state is not only a problem in a local part of the body but a local reflection of imbalance of the whole body.